2014
DOI: 10.1158/1538-7445.am2014-3748
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3748: Clinicopathological characterization of non-alcoholic Steatohepatitis (NASH)-derived hepatocellular carcinoma (HCC) as a patient stratification model in mice

Abstract: Therapeutic strategy against Hepatocellular carcinoma (HCC) is determined by tumor stage and liver function. Improvement of patient stratification thus contributes to improved survival of patients as well as to provide insights into the usage of anti-HCC drugs. Distinct from current clinical strategy, however, stratification has been paid a little attention in tumor animal models largely due to the lack of suitable model. Given the importance of animal study for the development of anti-HCC therapeutics, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…They show that MCD diet-fed mice exhibit increased serum ANG2 levels, confirming the expected findings alluded to above. They also studied another NASH model, namely neonatal streptozotocin and 16 weeks of western diet exposure, (9) and confirmed that ANG2 serum levels were increased in that model also. Administration of L1-10 reduced inflammation, ballooning, and fibrosis in MCD diet-fed mice but did not change the degree of steatosis.…”
Section: See Article On Page 1087mentioning
confidence: 70%
“…They show that MCD diet-fed mice exhibit increased serum ANG2 levels, confirming the expected findings alluded to above. They also studied another NASH model, namely neonatal streptozotocin and 16 weeks of western diet exposure, (9) and confirmed that ANG2 serum levels were increased in that model also. Administration of L1-10 reduced inflammation, ballooning, and fibrosis in MCD diet-fed mice but did not change the degree of steatosis.…”
Section: See Article On Page 1087mentioning
confidence: 70%
“…The Stelic Animal Model (STAM) of NASH-derived HCC is the first mouse model to depict the sequential evolution of clinical and pathomorphological features of the development of HCC in diabetesassociated NASH patients. 13,14 Briefly, 2-day-old male C57BL/6J mice were injected with streptozotocin (200 Āµg/mouse). Starting from 4 weeks of age, the mice were continuously fed a high-fat diet (HFD-32; Clea, Tokyo, Japan).…”
Section: Mouse Model Of Nafld-derived Carcinogenesis and Liver Samplesmentioning
confidence: 99%
“…It is also notable that female mice undergoing the same treatment did not develop NASH, fibrosis and HCC, which indicates that estrogen may play a protective role in susceptibility to NASH initiation and progression, as well as its malignant transformation in diabetic mice [58]. This group further characterized the tumor nodule size and metastatic status at 20 weeks of induction, and claimed that the stage of HCC seen in these mice corresponds to stages B to C of the Barcelona Clinic Liver Cancer (BCLC) staging system for humans [60]. This stratification could be helpful in assessing the efficacy of a therapeutic algorithm in the treatment of liver cancer with this model.…”
Section: Characteristics Of Currently Available Rodent Nash-hcc Modelsmentioning
confidence: 99%